Faktor Resiko yang Mempengaruhi Kejadian Stroke: Sebuah Tinjauan Sistematis - Yofa Anggriani Utama; Sutrisari Sabrina Nainggolan (Universitas Batanghari Jambi, 2022)
Stroke causes demage to the brain that appears suddenly, progressively and rapidly due to a non traumatic cerebral blood circulation disorder, vision. The purposse of this study was to determine the factors that influence the risk of stroke. The research design included in this systematic review used a research design, namely quantitative methods. Based on the results of a systematic review from articles, it was found that the risk factors that in fluence the occurrence of stroke are gender, age, education level, history of hypertension, blood cholesterol levels, obesity, coronary heart disease, smoking habits, consuming foods that contain high salt, and lack of physical activity. It is hoped that they can maintain a healhty lifestyle, as well as carry out regular health checks, namely controlling blood pressure and controling blood glucose levels.